The LNK1 night light-inducible and clock-regulated gene is induced also in response to warm-night through the circadian clock nighttime repressor in Arabidopsis thaliana - Mizuno, Takeshi (Landes Bioscience, 2014)
Ambient temperature has two fundamental impacts on the Arabidopsis circadian clock system in the processes referred to as temperature compensation and entrainment, respectively. These temperature-related longstanding problems have not yet been fully clarified. Recently, we provided evidence that temperature signals feed into the clock transcriptional circuitry through the evening complex (EC) nighttime repressor composed of LUX-ELF3-ELF4, and that the transcription of PRR9, PRR7, GI and LUX is commonly regulated through the nighttime repressor in response to both moderate changes in temperature (∆6 °C) and differences in steady-state growth-compatible temperature (16 °C to 28 °C). These temperature-associated characteristics of the core clock genes might be relevant to the fundamental oscillator functions. Here, we further show that the recently identified LNK1 night light-inducible and clock-controlled gene, which actually has a robust peak at daytime, is induced also by warm-night through the EC nighttime repressor in a manner very similar to PRR7, which is also night light-inducible daytime gene. Based on these findings, a hypothetical view is proposed with regard to the temperature entrainment of the central oscillator.